A robust in planta Agrobacterium‐mediated transformation in red chili (Capsicum annuum L.) - Hamdani, Anti Damayanti; Nugroho, Syarul; Esyanti, Rizkita Rachmi; Faizal, Ahmad; Suhandono, Sony (Indonesian Journal of Biotechnology, 2024)
Plant improvement through in vitro culture and genetic engineering is a significant aspect of breeding programs aimed at producing disease‐resistant cultivars of disease‐prone red chili (Capsicum annuum L.). However, the Capsicum genus is recalcitrant to genetic transformation and in vitro regeneration. Moreover, developing a universal transformation protocol is difficult due to its highly genotype‐dependent nature. Therefore, this study aimed to develop an Agrobacterium‐mediated in planta transformation method applicable to various red chili cultivars. Two open‐pollinated varieties, Tanjung 2 and Ciko, were subjected to transformation. The young seedlings were immersed in transformation medium containing Agrobacterium tumefaciens strain GV3101 harboring the binary vector pCAMBIA1301, which carries the β‐glucuronidase (GUS) gene. GUS histochemical analysis revealed that all the primary transformants of Tanjung 2 and Ciko were identified as chimeric. The average staining in the body of the seedlings was 88.63 + 26.33% in Tanjung 2, and 90.65 + 16.77% in the Ciko variety. More than 50% of the seedlings continued to express GUS in their shoot areas 10 days after Agrobacterium infection, indicating the possibility of transgene inheritance in the following generation. The in planta transformation approach is notably genotype independent, making it a promising standard transformation protocol for different red chili varieties.